If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6(7b+1)+3=-327
We move all terms to the left:
6(7b+1)+3-(-327)=0
We add all the numbers together, and all the variables
6(7b+1)+330=0
We multiply parentheses
42b+6+330=0
We add all the numbers together, and all the variables
42b+336=0
We move all terms containing b to the left, all other terms to the right
42b=-336
b=-336/42
b=-8
| y=-2×+2y=×-4 | | 3/2(x+1)=3 | | 2/3(x+1)=3 | | 23(x+1)=3 | | 10c+5=105 | | 2a+12=33/7 | | √x+13=15 | | x-2x=6x-18 | | 2(7)+6=5y | | k+14=54 | | 5(y+2/5(=-13 | | -40-2x+110=-8x+100 | | k-4¾=81/4 | | (2x+6)=(x-3=3) | | 4(8y-4.8)=2(0.9y+5.4)+5 | | -4(2x-3)+6=3(-4x+2) | | 5x+20=5x+4x | | ?x6.5=3.2 | | 293x+17=29 | | 5x+20=5x0 | | xx3.2=6.5 | | 5x+20=5x5 | | 5x+20=5x4x | | 26=c/23 | | 29+20=5a+6 | | 191=m+254 | | (2x+11)°=(6x–7)° | | 1/18x-5/7=3/4 | | 6x+20=8x–16 | | 14h=-112 | | 13x-40=50 | | 6(c−13)=−12 |